Humans anticipate the goal of other people`s point-light actions - Elsner, C.; Falck-Ytter, T.; Gredebäck, G. (Frontiers in Psychology, 2012)
This eye tracking study investigated the degree to which biological motion information from manual point-light displays provides sufficient information to elicit anticipatory eye movements. We compared gaze performance of adults observing a biological motion point - light display of a handreaching for a goal object or an on-biological version of the same event.Participants anticipated the goal of the point-light action in the biological motion condition but not in a non-biological control condition. The present study demonstrates that kinematici nformation from biological motion can be used to anticipate the goal of other people`s point-light actions and that the presence of biological motion is sufficient for anticipation to occur.